2002
DOI: 10.1097/01.asn.0000013295.11876.c9
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Kidney Transplantation

Abstract: Abstract. It remains unclear whether preemptive transplantation is beneficial, and if so, who benefits. A total of 38,836 first, kidney-only transplants between 1995 and 1998 were retrospectively studied. A surprising 39% of preemptive transplants were from cadaver donors, and the proportions of cadaver donor transplants that were preemptive changed little, from 7.3% in 1995 to 7.7% in 1998. Preemptive transplants using cadaver donors were more likely among recipients aged 0 to 17 yr versus 18 to 29 yr (odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
299
3
14

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(327 citation statements)
references
References 18 publications
11
299
3
14
Order By: Relevance
“…Preemptive renal transplantation occurred in 25% of adult recipients of allografts from living donors in the United States in the latter part of the twentieth century (2,3). The lower rate of PRT of cadaveric renal allografts into adult recipients, approaching 10%, is likely attributable to the prolonged waiting times of transplant candidates on the cadaveric list, during which persons become dialysisdependent.…”
Section: Rates Of Preemptive Renal Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Preemptive renal transplantation occurred in 25% of adult recipients of allografts from living donors in the United States in the latter part of the twentieth century (2,3). The lower rate of PRT of cadaveric renal allografts into adult recipients, approaching 10%, is likely attributable to the prolonged waiting times of transplant candidates on the cadaveric list, during which persons become dialysisdependent.…”
Section: Rates Of Preemptive Renal Transplantationmentioning
confidence: 99%
“…An analysis of 4095 PRT recipients of a renal allograft during 1994 through 2000 in the United States revealed that the estimated glomerular filtration rates (GFRs) averaged 9.9 mL/min [SD (5,3)] at the time of transplantation (6); levels that were significantly less than the suggested threshold of 14 mL/min for dialysis initiation proposed by the KDOQI working group (1). These observations were corroborated by a second study that also demonstrated individuals transplanted preemptively with a cadaveric renal allograft have severe renal insufficiency at the time of transplantation (median serum creatinine level of 8.6 mg/dL), indicating the need for a therapeutic intervention (7).…”
Section: Residual Renal Function At the Time Of Prtmentioning
confidence: 99%
See 1 more Smart Citation
“…L iving organ donors are the inspiration of transplantation, leading to earlier transplantation and better recipient survival (1)(2)(3)(4). This is particularly true for kidney transplantation, where 55,912 (49.5%) of the 112,948 kidney donors between 2000 and 2008 were living donors.…”
mentioning
confidence: 99%
“…16 Pre-emptive transplantation is associated with a 25% reduction in transplant failure and 16% reduction in mortality compared to recipients receiving a transplant after starting dialysis. 17 Transplantation of the kidney, when properly applied, is thus the treatment of choice for patients with ESRD because of lower costs and better outcomes.…”
Section: Outcomes Of Kidney Transplantationmentioning
confidence: 99%